Future prospect of anisotropic 2D tin sulfide (SnS) for emerging electronic and quantum device applications - Sarkar, Abdus Salam (Frontiers in Electronics, 2025)
The family of anisotropic two-dimensional (2D) emerging materials is rapidly evolving due to their low crystal symmetry and in-plane structural anisotropy. Among these, 2D tin sulfide (SnS) has gained significant attention because of its distinctive crystalline symmetry and the resulting extraordinary anisotropic physical properties. This perspective explores recent developments in anisotropic 2D SnS. In particular, it highlights advances in isolating high-quality SnS monolayers (1L-SnS) and in applying advanced techniques for anisotropic characterization. The discussion continues with an overview of the anisotropic optical and electronic properties of SnS, followed by recent progress in emerging electronic device applications, including energy conversion and storage, neuromorphic (synaptic) systems, spintronics and quantum technologies. In addition to presenting significant research findings on SnS, this perspective outlines current limitations and discusses emerging opportunities and future prospects for its application in quantum devices.